Structural characterization of the human eukaryotic initiation factor 3 protein complex by mass spectrometry. - Damoc, E; Fraser, C; Zhou, M; Videler, H; Mayeur, G; Hershey, J; Doudna, J; Robinson, C; Leary, J (2007)
Protein synthesis in mammalian cells requires initiation factor eIF3, an approximately 800-kDa protein complex that plays a central role in binding of initiator methionyl-tRNA and mRNA to the 40 S ribosomal subunit to form the 48 S initiation complex. The eIF3 complex also prevents premature association of the 40 and 60 S ribosomal subunits and interacts with other initiation factors involved in start codon selection. The molecular mechanisms by which eIF3 exerts these functions are poorly understood. Since its initial characterization in the 1970s, the exact size, composition, and post-translational modifications of mammalian eIF3 have not been rigorously determined. Two powerful mass spectrometric approaches were used in the present study to determine post-translational modifications that may regulate the activity of eIF3 during the translation initiation process and to characterize the molecular structure of the human eIF3 protein complex purified from HeLa cells. In the first approach, the bottom-up analysis of eIF3 allowed for the identification of a total of 13 protein components (eIF3a-m) with a sequence coverage of approximately 79%. Furthermore 29 phosphorylation sites and several other post-translational modifications were unambiguously identified within the eIF3 complex. The second mass spectrometric approach, involving analysis of intact eIF3, allowed the detection of a complex with each of the 13 subunits present in stoichiometric amounts. Using tandem mass spectrometry four eIF3 subunits (h, i, k, and m) were found to be most easily dissociated and therefore likely to be on the periphery of the complex. It is noteworthy that none of these four subunits were found to be phosphorylated. These data raise interesting questions about the function of phosphorylation as it relates to the core subunits of the complex.